Incidence and severity of Arcanobacterium pyogenes injection site abscesses with needle and needle-free injection methods - Gerlach, Bryce Mark (Kansas State University, 2010)
Nursery age pigs (n=198) were used to evaluate the difference in the occurrence of injection site abscesses between needle-free jet injection and conventional needle-and-syringe injection systems. Pigs were fed for 21 d prior to treatment administration to acclimate the pigs to the environment of the Kansas State University Segregated Early Weaning (SEW) unit. On d 21 each pig was injected with aluminum hydroxide adjuvant in the neck and ham with needle-free jet injection (Pulse Needle-Free Systems, Lenexa, KS) and conventional needle-and-syringe injection. Needle-free and conventional needle-and-syringe injections were randomly assigned to pig side yielding a total of 396 injections per treatment with a total of 792 injections sites. Immediately prior to injection, the external surface of the injection sites were contaminated with an inoculum of Arcanobacterium pyogenes, a bacterium commonly associated with livestock abscesses. The pigs were then fed for a period of 27 or 28 d. On d 27 or d 28 the pigs were humanely euthanized and sent to the Kansas State Veterinary Diagnostics Laboratory where necropsies were performed and the injection sites harvested for histopathological evaluation. The needle-free jet injection system was associated with more injection site abscesses than the conventional needle-and-syringe injection method for both neck (P=0.0625) and ham (P=0.0313) injection sites. Twelve abscesses were found at injection sites administered via needle-free jet injection method while only 1 abscess was found with the conventional needle-and-syringe injection method. 5 abscesses were found at the neck injection sites and 8 abscesses were found at ham injection sites. There were no significant differences seen in tissue granulation resulting from reaction to the adjuvant. In summary, the implementation of needle-free jet injection systems in market hog production will be beneficial to eliminate needles and needle fragments in meat products but, when in the presence of Arcanobacterium pyogenes, it may increase the occurrence of injection site abscesses in pork carcasses that will need to be trimmed in pork processing plants. Although more abscesses were associated with needle-free jet injection, their occurrence was observed at a very low rate given that all injection sites were intentionally contaminated prior to injection.
Keywords: Abscess; Arcanobacterium pyogenes; Carcass Trimming; Needle-free jet injection; needle fragments; Agriculture, Animal Pathology (0476)